The Oxford handbook of the Indian economy - Ghate, Chetan (New York, NY : Oxford University Press, 2012)
This handbook reflects India's growing economic importance on the world stage, and features research on core topics by leading scholars to understand the Indian economic miracle and the obstacles India faces in transforming itself into a modern 21st-century economy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Economic development -- India; Globalization -- Economic aspects -- India; India -- Economic policy -- 1991-